ADEQUACY AND SUITABILITY OF GREEN OPEN SPACE IN MEDAN KOTA DISTRICT - Oktavia Siska Yanti; Agus Purwoko; Dwi Lindarto (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to analyze the availability of green open space through the interpretation of green open space in several years in the Medan Kota District, evaluate the implementation of green open space related to the adequacy aspect, analyze projections of green open space needs based on population growth, and analyze spatial-based spatial management policies in urban villages in Medan Kota District in an effort to meet the adequacy and suitability standards of green open spaces. The type of research used is descriptive with a qualitative approach. The location of this research was in Medan Kota District, Medan City. The analysis used in this study is spatial analysis through the application of Geographic Information Systems (GIS). The results of the study show that the availability of green open space in the Medan Kota District within 3 years has changed the area of green open space. In 2018, the area of green open space in the Medan Kota District was 128.105 ha. The area of green open space in Medan Kota District in 2021 will be 89,768 ha. The adequacy of green open space based on the area of Medan Kota District is 598,068 ha. The provision standards for green open space in Medan Kota District have not been met. Of the 20% standard, Medan Kota District only has 89,768 ha, or still lacks 29,846 ha. The projected need for green open space based on the population of Medan Kota District has been fulfilled, but the distribution is not evenly distributed. The directive to fulfill a minimum area of 20% green open space from total area can be carried out through the following mechanisms: purchasing and/or land acquisition; management; land leasing; community cooperation; and/or increasing the quantity and quality of green open space.